2018
DOI: 10.12997/jla.2018.7.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Circulating FGF21 Concentrations and the Severity of Coronary Artery Damage in Subjects with Cardiovascular Disease

Abstract: Objective: Fibroblast growth factor (FGF) 21 is a recently established therapeutic target for treating metabolic syndromes, which include potential precursors to cardiovascular disease, suggesting a link between FGF21 and atherosclerosis. However, the association between serum FGF21 concentrations and coronary artery disease remain controversial. The aim of this study is to evaluate the association between circulating FGF21 concentrations and coronary artery lesions and clinical severity. Methods: We enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a study of 417 patients, the serum FGF21 levels of the patients with CAD and without CAD were similar regardless of the presence of diabetes, and there was no association between the serum FGF21 levels and the severity of CAD defined by the number of stenotic vessels and segments (20). In Park et al (21) study, no relationship was found between serum FGF21 levels and the severity of CAD determined by SYNTAX scores. In another study, Kim et al (22) initially observed a sig-nificant correlation between serum FGF21 levels and GENSINI and EXTENT scores of 120 patients; however, in the final analysis, they found that there was no relationship between FGF21 levels and the risk scores in diabetic patients (r = 0.332, p = 0.055; and r = 0.296, p = 0.084, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…In a study of 417 patients, the serum FGF21 levels of the patients with CAD and without CAD were similar regardless of the presence of diabetes, and there was no association between the serum FGF21 levels and the severity of CAD defined by the number of stenotic vessels and segments (20). In Park et al (21) study, no relationship was found between serum FGF21 levels and the severity of CAD determined by SYNTAX scores. In another study, Kim et al (22) initially observed a sig-nificant correlation between serum FGF21 levels and GENSINI and EXTENT scores of 120 patients; however, in the final analysis, they found that there was no relationship between FGF21 levels and the risk scores in diabetic patients (r = 0.332, p = 0.055; and r = 0.296, p = 0.084, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…The determination of whether FGF21 has clinical significance as a biomarker is complicated by several potential confounding circumstances. The study conducted by Park et al [ 20 ] could not find any correlation between serum FGF21 levels and the severity of CAD as evaluated by SYNTAX scores.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, many observational studies have reported that FGF21 plays a role in metabolic homeostasis [72]. Berglund et al [73] showed that subcutaneous administration of FGF21 for 3-7 days signi cantly reduced fasting blood glucose, triglyceride and insulin levels, thereby improving glucose metabolism in animal models of diabetes.…”
Section: Fgf21mentioning
confidence: 99%